Rock Mass Characterization for Assessment of Safe Cut Slope and Rock Bearing Capacity at Gondang Dam Site, Karanganyar, Indonesia - I Gde Budi Indrawan; Sao Sochan; Dwi Agus Kuncoro (Geological Engineering Department Universitas Gadjah Mada, 2019)
This paper presents results of surface rock mass characterization for assessment of safe cut slopes and allowable bearing capacity of foundation rocks at the construction area of Gondang Dam. The rock mass characterization involved determination of intact rock engineering properties and rock mass quality based on the Geological Strength Index. The rock mass characterization results showed that the research area consisted of moderately to highly weathered and very weak to weak andesite breccia and andesite tuff breccia. The andesite breccia had very poor to fair rock mass quality, while the andesite tuff breccia had poor to fair rock mass quality. The research area was divided into three zones of safe cut slope and allowable bearing capacity. Landslides occurred at natural slopes having poor to very poor rock mass quality and inclinations greater than the determined safe cut slopes.The foundation rock of the embankment dam had fair rock massquality and 135–280 T/m2 allowable bearing capacity